Non Bambusoid grasses (Gramineae) from Raja Ampat Archipelago, Papua Barat Province, Indonesia - Sumadijaya, Alex; Veldkamp, Jan Frits (Research Center for Biology, 2012)
Thirty two species of non-bambusoid grasses from 28 genera were recorded for the Raja Ampat Archipelago, Papua Barat Province, Indonesia, mostly from secondary forest. The result was compiled from Widya Nusantara Expedition (EWIN), Takeuchi (2003), and Van Royen (1960). This is a first attempt to record non-bambusoid grasses for a remote archipelago in Indonesia.